2019
DOI: 10.2478/msp-2019-0034
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and optical properties of CdSe/CdS core/shell nanocrystals

Abstract: This paper attempts to describe an effective method for producing a composite of quantum dots consisting of CdSe (core) with CdS (shell). This nanoparticles composite was synthesized from modified organometallic precursors. The sizes of the nanoparticles were estimated from X-ray diffraction data using Debye-Scherer formula and compared with high resolution electron microscopy (HRTEM) and optical spectra. The shape of CdSe/CdS NPs is nearly spherical and revels that the CdS shell with the thickness ~0.6 nm alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The prepared particle diameter(5nm) is consistent with the reported core/shell structure model for the CdSe/CdS sample [25]. This result is in agreement with that of Gadalla et al [18] . It can also be seen that the black points represent the core, while the shadows around the core may be attributed to the shell formed around the core.…”
Section: Results and Dissectionssupporting
confidence: 92%
See 1 more Smart Citation
“…The prepared particle diameter(5nm) is consistent with the reported core/shell structure model for the CdSe/CdS sample [25]. This result is in agreement with that of Gadalla et al [18] . It can also be seen that the black points represent the core, while the shadows around the core may be attributed to the shell formed around the core.…”
Section: Results and Dissectionssupporting
confidence: 92%
“…and optical spectra. UV-Vis spectroscopy showed a systematic red shift in the absorption and emission spectra after the deposition of CdS which confirms the shell growth over the CdSe core [18]. In this study, the effect of CdS shell deposited on the CdSe core was investigated by characterizing the structural, morphological and optical properties of CdSe and CdSe/CdS QDs which were fabricated using the chemical reaction method.…”
mentioning
confidence: 75%
“…Vishwakarma et al [18] investigated the effect of CdS doping on the microstructural behavior of titanium dioxide thin film and he reported the decrease in crystallite size from 46 (undoped TiO 2 ) to 38 nm with 2 wt% CdS and also it is found that Raman spectra reflect that Raman peak shifted toward higher wavenumber with CdS doping. Gadalla et al [19] studied the synthesis, structural, and optical characterization of CdS and ZnS nanoparticles that were successfully prepared using an organometallic method. In the study, they concluded that the XRD analysis confirmed that CdS and ZnS NPs were of the hexagonal wurtzite structure.…”
Section: Introductionmentioning
confidence: 99%
“…Gadalla et al. [ 19 ] studied the synthesis, structural, and optical characterization of CdS and ZnS nanoparticles that were successfully prepared using an organometallic method. In the study, they concluded that the XRD analysis confirmed that CdS and ZnS NPs were of the hexagonal wurtzite structure.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption property of the CdSe/CdS show that the intensity of fluorescence spectrum of the core-shell system was improved resulting in a sensible conversion efficiency enhancement. Core−shell QDs have been a noteworthy improvement in the region of fluorescence, with a kind I band arrangement being the most persuasive form [11,12]. In this structure, the band gap of the ore is littler than the band gap of the shell, just as the band gap value of the center falls inside the band gap value of the shell (like CdSe/CdS, CdSe/ZnS, and InP/ ZnS [13].…”
Section: Introductionmentioning
confidence: 99%